New Radiocarbon Dates and Bayesian Models for Nelson Bay Cave and Byneskranskop 1: Implications for the South African Later Stone Age Sequence. Issue 2 (9th March 2016) - Loftus, Emma; Sealy, Judith; Lee-Thorp, Julia
Abstract: The southern African Later Stone Age sequence is widely considered to be well dated based on radiocarbon dates from dozens of archaeological sites, and apparently shows more or less synchronous cultural shifts across an extensive area. Yet, closer examination reveals the inadequacy of many of the decades-old and uncalibrated individual site chronologies that underpin this regional chronology, making robust comparisons of the chronology of technological change across this region impossible. Here, we present 26 new AMS 14 C dates and Bayesian modeled chronologies for two important archaeological cave sites in southernmost Africa, Nelson Bay Cave and Byneskranskop 1. The results provide more robust age estimates for these cultural and paleoenvironmental sequences and revise interpretations of these sites in several instances. This project demonstrates the necessity of redating key sites, and the value of currently underutilized methods, including calibration and Bayesian modeling, for southern African archaeology.